2018
DOI: 10.1002/marc.201800246
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Gels and Their Applications in Stretchable Electronics

Abstract: Ionic gels represent a novel class of stretchable materials where ionic conducting liquid is immobilized in a polymer matrix. This review focuses on the design of ionic gel materials and device fabrication of ionic-gel-based stretchable electronics. In particular, recent progress in ionic-gel-based electronic skin (pressure/strain sensors, electric double-layer transistors, etc.), flexible displays, energy storage devices, and soft actuators are summarized, followed by a discussion of challenges in developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(92 citation statements)
references
References 133 publications
(205 reference statements)
0
92
0
Order By: Relevance
“…The reliance on ion diffusion in IGs as the mechanism of transformation dictates limited response speeds relative to other IEAP material systems. Nonaqueous IGs have been prepared by embedding organic electrolyte and/or ionic liquid (IL) solutions within a polymer matrix 212…”
Section: Ionic Electroactive Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The reliance on ion diffusion in IGs as the mechanism of transformation dictates limited response speeds relative to other IEAP material systems. Nonaqueous IGs have been prepared by embedding organic electrolyte and/or ionic liquid (IL) solutions within a polymer matrix 212…”
Section: Ionic Electroactive Polymersmentioning
confidence: 99%
“…These implementations of IEAPs have used a variety of techniques and materials247 including CPs, CNTs, graphene, metallic particles, NWs, microplates, and mixtures thereof 248–261. A recent review by Peng and co‐workers has directly compared aqueous and nonaqueous ionic gels scoped to applications in stretchable electronics 212. Wearable technology using IEAPS was demonstrated by Ming et al by embedding IPMC sensors in a smart glove (shown schematically in Figure a) 262.…”
Section: Ionic Electroactive Polymersmentioning
confidence: 99%
“…However, the challenges of creating stable bonding between hydrogels and elastomeric substrates need to be addressed for the stability and high output performance of these self‐powered ITS systems. Although tough and robust hydrogels have been developed, the weak interfacial bindings between hydrogels and elastomers severely limit their integration and multifunctionality . Various research groups reported a strategy to create stable adhesion of the hydrogel‐elastomer layers via covalent chemical anchorage .…”
Section: Self‐powered Ionic Tactile Sensorsmentioning
confidence: 99%
“…The use of conductive gels, namely, ionogels and hydrogels, has been largely applied to address the issue. Ionic liquids, or ionogels, are salts with low vapor pressure displaying high ionic conductivity . Ionogels have been used as gate dielectrics in graphene‐based thin film transistors operating at high frequencies .…”
Section: D Graphene For Advanced Electronicsmentioning
confidence: 99%